2014
DOI: 10.4103/2141-9248.126615
|View full text |Cite
|
Sign up to set email alerts
|

Constraints, challenges and prospects of public-private partnership in health-care delivery in a developing economy

Abstract: Background:In Nigeria, concerns on the quality and financing of health-care delivery especially in the public sector have initiated reforms including support for public-private partnerships (PPP) at the Federal Ministry of Health. Likewise, Enugu State has developed a draft policy on PPP since 2005. However, non-validation and non-implementation of this policy might have led to loss of interest in the partnership.Aim:The aim of this study was to provide evidence for planning the implementation of PPP in Enugu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This perception among participants could be attributed to the fact that in Pakistan, existing PPP initiatives started only as a result of poor performance of the government sector. Other researchers have found that overall understanding of PPP is good among public and private sector health workers 23 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This perception among participants could be attributed to the fact that in Pakistan, existing PPP initiatives started only as a result of poor performance of the government sector. Other researchers have found that overall understanding of PPP is good among public and private sector health workers 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Resistance against government initiatives that allow increased role of private sector in healthcare provision has been reported in Pakistan 15 and other settings. For example, around 50% public sector health workers opposed the idea of PPP in delivery of healthcare services in Enugu state of Nigeria 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rules define private property rights and their allocation; the relationship between participants in the partnership; conventions governing participation such as competition, fair business practices and mutual trust [16,17]. The necessity for ensuring effective institutional arrangements in the context of health service delivery is aimed at implementing strategies to improve the quality of healthcare services, increase universal and equitable access to healthcare service delivery [1,18,19]. The government of Tanzania has therefore, adopted three modes of health service delivery under PPP namely contracting out, offering subsidies and privatisation.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the central government is mandated to periodically monitor and supervise activities in line with PPP service agreements with partners. In line with decentralisation guidelines, primary health services are supposed to be monitored by LGAs, while regional hospitals are under the supervision of regional authorities[18,26,30,31,36]. The discussion with government officials revealed that reports from partners were sometimes not submitted, or written and hence, the monitoring team lacked a foundation to assess progress.…”
mentioning
confidence: 99%